Assessing the Evidence: The Effectiveness and Impact of Public Governa nce-Oriented Multi-Stakeholder Initiatives - Brockmyer, Brandon; Fox, Jonathan A. (Transparency & Accountability Initiative, 2015)
Transnational multi-stakeholder initiatives (MSIs) – voluntary partner ships between governments, civil society, and the private sector – are an increasingly prevalent strategy for promoting government responsiv eness and accountability to citizens. While most transnational MSIs in volve using voluntary standards to encourage socially and environmenta lly responsible private sector behavior, a handful of these initiative s – the Extractive Industries Transparency Initiative (EITI), the Cons truction Sector Transparency Initiative (CoST), the Open Government Pa rtnership (OGP), the Global Initiative on Fiscal Transparency (GIFT) a nd the Open Contracting Partnership (OCP) – focus on information discl osure and participation in the public sector. Unlike private sector MS Is, which attempt to supplement weak government capacity to enforce ba sic social and environmental standards through partnerships between bu sinesses and civil society, public sector MSIs ultimately seek to bols ter public governance. But how exactly are these MSIs supposed to work ? And how much has actually been achieved?The purpose of this study is to identify and consolidate the current state of the evidence for pub lic governance-oriented MSI effectiveness and impact. Researchers coll ected over 300 documents and interviewed more than two-dozen MSI stake holders about their experiences with five public governance oriented m ulti-stakeholder initiatives.This report provides a ‘snapshot’ of the evidence related to these five MSIs, and suggests that the process of leveraging transparency and participation through these initiatives fo r broader accountability gains remains uncertain. The report highlight s the ongoing process of defining MSI success and impact, and how thes e initiatives intersect with other accountability actors and processes in complex ways. The study closes with key recommendations for MSI st akeholders.
Keywords: Accountability; Participation; Program evaluation; Transparency; global governance; multi-stakeholder